Comprehensive Study of Various Blockchain Development Platforms - Meva, Divyakant; John, Anand (International Journal of Computer Sciences and Engineering, 2025)
This research paper examines the technical architecture, performance characteristics, and development ecosystems of leading blockchain platforms. The research elaborates the different aspects of blockchain technology through comparative analysis of Ethereum, Hyperledger Fabric, Solana, Polkadot, Cosmos, and Corda and hence, we evaluate their distinct approaches to consensus, scalability, security, and programmability. The study reveals significant trade-offs between decentralization, performance, and developer accessibility across platforms. The smart contract development paradigm is described in the study. We identify emerging trends including modular blockchain architectures, application-specific chains, and cross-chain interoperability solutions. The performance of developer ecosystems and tooling security models is illustrated. The study also reveals real world applications and its use case alignment. The different emerging trends in blockchain technology development in the use of real world technology is discussed in the study. This comprehensive assessment provides guidance for organizations selecting blockchain platforms based on specific use case requirements, technical constraints, and strategic objectives.